'I would be a completely different teacher if I had been with a different mentor': Ways in which educative mentoring matters as novices learn to teach. Issue 2 (14th March 2020) - Wexler, Lindsay Joseph
ABSTRACT: This study investigates the role of educative mentors as two novices learn to teach, following them from their yearlong student teaching (2015–2016) through their first-year teaching (2016–2017). During student teaching, each novice was paired with a mentor teacher who received preparation and support to engage in educative mentoring practices. This study analyzes evidence from multiple data sources collected over 2 years to understand what novices take up from their student-teaching mentors and take with them into their first-year teaching. Findings illustrate that the activities of mentoring matter in the learning to teach process of novices, particularly related to the way novices are able to focus their planning, instruction, and reflection around pupil thinking and understanding.